DEVELOPMENT OF THE PROCEDURES OF QUALITY CONTROL OF MAGNETIC MEDICATIONS (MAGNETIC MEDICAL OINTMENTS, MAGNETIC SUPPOSITORIES, IRON-CARBON COMPOSITE FOR THE CRYOSURGERY) - Yu. Ya. Kharitonov; O. G. Cherkasova; S. P. Zavadskiy; E. Yu. Shabalkina; I. I. Krasnyuk (Jr.); V. Yu. Grigorjeva; S. N. Tsybusov; E. A. Abizov (Разработка и регистрация лекарственных средств)
The experimental tests for quality control of magnetic medical ointments, magnetic suppositories (with procaine, diclofenac), iron-carbon composite (active ingredient of heat conductivity systems for the magnetic control heat transference in the cryosurgery) have been developed.